Metode Pembelajaran Sejarah Kebudayaan Islam (SKI) di Mi Islamiyah Ngasem Bojonegoro - Zumrotus Sa’diyah; Firda Zakiyatur Rofiah (Medan Resource Center, 2021)
The main problem in this study is how the teacher's strategy in choosing SKI learning methods at MI Islamiyah Ngasem and how students respond to variations in methods in SKI learning at MI Islamiyah Ngasem. The method used in this study is a qualitative method, the data collection techniques used are interviews, observation, and documentation. The results of this study are: 1) The teacher's strategy in choosing the method of learning SKI at MI Islamiyah Ngasem varies, including: the teacher sees the health condition of the students; the teacher sees the psychological condition of the students; the teacher sees the scheduled time for SKI subjects, the teacher sees the contents of the SKI subject matter to be delivered; 2) Students' responses to variations in methods for learning SKI at MI Islamiyah Ngasem are shown by the enthusiasm to learn when SKI lessons are delivered using a variety of learning methods, are not sleepy when SKI subjects are delivered, feel happy and not bored when SKI lessons are delivered using various methods. , feel less about the SKI lesson hours organized by the school, and feel the need to increase the hours of SKI lessons.